Scooby-Doo! straight outta nowhere [videorecording (DVD)] : Scooby-Doo meets Courage the cowardly dog - Dilworth, John R., 1963- ([Warner Home Video], 2021)
An original animated feature so exciting it's scratching at the door! Comedy is unleashed when Scooby-Doo, the favorite mystery solving mutt, teams up for the first time with Courage the Cowardly Dog. The canine colleagues sniff out a strange object in the middle of Nowhere, Kansas, the backwoods hometown of Courage and his owners, Eustace and Muriel Bagge. Soon, the mysterious discovery puts them on the trail of a giant cicada monster and her wacky winged warriors. Fred, Velma, Daphne and Shaggy know that this job is too big for a flyswatter. They₂ll need the help of the doggy duo to piece together the puzzle. Can Scooby and Courage overcome their jitters and defeat the insect army before the whole world bugs out? Try not to get scared.